Adaptation to climate change - Lazkano, Itziar (2016)
Adaptation costs to climate change vary widely across countries, especially between developed and developing countries. Adaptation costs also influence a country's decision to abate and join international environmental agreements (IEAs). In this paper, the authors study how these cost differences affect participation incentives. Their model identifies two channels through which adaptation affects free-riding incentives: carbon leakage and cost asymmetry in adaptation. In contrast with the common view, the authors find that the presence of adaptation is not necessarily an impediment to cooperation on abatement. They also present conditions under which adaptation can strengthen or weaken free-riding incentives. The results serve as a cautionary tale to policy makers and suggest that policies directed at reducing carbon leakage and/or cost differences between developed and developing countries may also affect the success and failure of IEAs.